Temporal patterns of cognitive decline after hypertension onset among middle-aged and older adults in China - Shouqiang Zhu; Jinhua Bo; Tianjiao Xia; Xiaoping Gu (Scientific Reports)
Abstract Individuals with prevalent hypertension are at an increased risk of developing dementia and tend to exhibit lower cognitive function. However, the magnitude of cognitive change following the onset of new hypertension remains uncertain. A cohort of 7949 adults aged 45 and older without hypertension at baseline was followed prospectively for 7 years. Cognitive assessments were conducted initially (wave 1) and at least once between wave 2 (2013) and wave 4 (2018). Cognitive function was evaluated using a global cognition score, derived as a composite measure from four distinct cognitive tests. Linear mixed-effects models were employed to estimate the changes in cognitive function at the onset of hypertension (intercept change) and the subsequent rate of cognitive decline (slope change) over the follow-up period. The models accounted for pre-hypertension cognitive trajectories and participant-specific factors, with interaction terms included for antihypertensive medication, age and educational level. Of the 7949 participants, 1993 (25.07%, mean age 58.8 ± 8.84 years, 48.0% male) developed new-onset hypertension. Both groups—those without hypertension and those with new-onset hypertension—experienced annual cognitive decline during the follow-up period. The onset of hypertension was not associated with an acute decrease in global cognition or performance on the four cognitive tests. However, after the onset of hypertension, participants exhibited a statistically significant accelerated decline in global cognition (− 0.029 SD/year; 95% CI − 0.043 to − 0.015; p < 0.001), attention and calculation (− 0.022 SD/year; 95% CI − 0.040 to − 0.004; p = 0.017), and orientation (− 0.022 SD/year; 95% CI − 0.038 to − 0.005; p = 0.010). No significant changes were observed in episodic memory (− 0.009 SD/year; 95% CI − 0.028 to 0.010; p = 0.346) or visuospatial abilities (− 0.013 SD/year; 95% CI − 0.032 to 0.006; p = 0.185). Interaction analyses indicated that the use of antihypertensive medication, age, and educational level moderated the extent of global cognitive decline post-hypertension onset. The onset of new hypertension was not associated with an immediate decline in cognitive function compared to individuals without hypertension. However, it was linked to more rapid declines in global cognition, orientation, and attention and calculation abilities over time. These findings underscore the potential importance of hypertension prevention for maintaining long-term brain health.